Penerapan Konsep Rumah Sehat Sederhana Pada Bedah Rumah Warga Di Desa Pakulonan Barat, Tangerang - Anisza Ratnasari; Marchelia Gupita Sari; Mulyadi Sugih Dharsono; Abdullah Hibrawan; Nurul Lestari Hasanuddin; Mohammad Nur Afla (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2019)
House is one of the primary human needs that must require physiological and psychological needs of its inhabitants. However, the needs that must be fulfilled should not only both of them, but also the criteria of a healthy house, that is, health and safety requirements. Desa Pakulonan Barat is one of the densely populated settlements in Tangerang, where there are still uninhabitable housing. In line with the government's program to reduce the number of uninhabitable housing, institution through community service together with corporate social responsibility (CSR) conducted rebuild or revovation on residents' houses with the concept of a simple healthy house. Open interview are conducted to get resident’s feedback on their psychological needs. Hopely, the activity can educate citizens to create healthy habitable dwellings use simple materials and economical costs.